Small-Bowel Neoplasms: Role of MRI Enteroclysis - Angela Faggian; Maria Rosaria Fracella; Grazia D’Alesio; Maria Eleonora Alabiso; Daniela Berritto; Beatrice Feragalli; Vittorio Miele; Francesca Iasiello; Roberto Grassi (Gastroenterology Research and Practice)
Small-bowel neoplasms are the 3%–6% of all gastrointestinal tract neoplasms. Due to the rarity of these lesions, the low index of clinical suspicion, and the inadequate radiologic examinations or incorrect interpretation of radiologic findings, a delay in diagnosis of 6–8 months from the first symptoms often occurs. Even if conventional enteroclysis and capsule endoscopy are the most common procedures used to accurately depict the bowel lumen and mucosal surface, their use in evaluating the mural and extramural extents of small-bowel tumors is limited. Instead multidetector computed tomographic enteroclysis and magnetic resonance enteroclysis have the potential to simultaneously depict intraluminal, mural, and extraintestinal abnormalities. In particular MR enteroclysis has an excellent soft tissue contrast resolution and multiplanar imaging capability. It can provide anatomic, functional, and real time information without the need of ionizing radiation. MR findings, appearances of the lesions, combined with the contrast-enhancement behavior and characteristic of the stenosis are important to differentiate small-bowel neoplasm from other nonneoplastic diseases.